Classifying 6T SRAM Cell over Processing Voltage and Temperature Curves - Subudhi, Asit; Mohanty, Saumendra (International Journal of Psychosocial Rehabilitation, 2025)
According to the shifting of centre of mass of the semiconductor firm headed for multimedia, consumer and communications applications, different requirements in term of memory have ascended. The incomparable need for memory being mostly compelled by computer industry. Power consumption is pretty limiting factor for quantity of memory that can be integrated on the single board. This project scrutinizes and classified six transistor SRAM cell over processing temperature and voltage dissimilarities. The parameters of a SRAM being considered are as Read Delay, SNM Read, Write Delay, leakage power dissipation and SNM Write.